Caritas : Histoires, paraboles et rêves - Cazenave, Sabine; Barker, Barry; Bennett, Martyn; Fauvel, Sophie; Seddon, Peter (Amiens : Éditions du Musée de Picardie, 2014)
Alÿs, Francis ; Broodthaers, Marcel ; Van Doetecum, Lucas ; Van Doetecum, Joannes ; Kentridge, William ; Lagarde, Pierre ; Lefebvre, Jules ; Lijn, Liliane ; Maulbertsch, Franz Anton ; Morot, Aimé Nicolas ; Oursler, Tony ; Paysant, Michel ; Rousseau, Samuel ; Sanson, Justin ; Serra, Richard ; Sirani, Elisabetta ; Vien, Joseph Marie ; West, Frank
Caritas, Histoires, paraboles et rêves, Musée de Picardie, Amiens, 10 octobre 2014 au 18 janvier 2015
boek